A Twenty-Five-Year Biography of the TOD Concept: From Design to Policy, Planning, and Implementation. (December 2019) - Jamme, Huê-Tâm; Rodriguez, Janet; Bahl, Deepak; Banerjee, Tridib
Promoting a new vision of community—walkable, affordable, environmentally sustainable—the urban design idea of transit-oriented development (TOD) extended the land use and transportation nexus. This review article offers a twenty-five-year retrospective of TOD literature, shaped by disciplinary, policy, and practice predilections. Although the "D" in TOD stands for the encompassing notion of "development, " most literature focused on land development in particular. Meanwhile, sustainable or community development ideas languished, and other Ds such as Density, Diversity, and Design served as an operational framework for outcome-based research. We conclude by urging renewed focus in TOD research on the original goal of developing inclusive and sustainable communities.